Analysis of Scooter Taxi User Satisfaction from the Aspect of Usability Through the Maxride Application in Makassar Using the Use Questionnaire Method - Achmad, Muh Fachran Fahiran; Saleh, Anis; Hafid, Muhammad Fachry (Journal of Sustainability Industrial Engineering and Management System, 2023)
This study aims to analyze the usability of the Maxride ride-hailing application in Makassar, Indonesia, focusing on user satisfaction from a usability perspective. The research employed a quantitative approach using the USE Questionnaire method. Data was collected from 400 Maxride users in Makassar through an online survey. The questionnaire assessed four usability variables: Usefulness, Ease of Use, Ease of Learning, and Satisfaction.The overall usability score of the Maxride application was 65.60%, falling in the "feasible" category. While the app scored well in Usefulness (68.98%), Ease of Learning (74.06%), and Satisfaction (70.98%), it performed poorly in Ease of Use (48.38%), indicating significant room for improvement in this area.The study was limited to Makassar users and relied solely on quantitative data. As a cross-sectional study, it only captured user perceptions at a single point in time. These limitations suggest opportunities for future research with broader geographical scope, mixed methods, and longitudinal designs. The findings provide actionable insights for Maxride's development team to improve the app's user interface and functionality, particularly in terms of ease of use. Addressing these issues could enhance user satisfaction, retention, and potentially drive business growth.Improving the usability of ride-hailing apps like Maxride can contribute to better urban mobility solutions, potentially impacting transportation habits and quality of life in cities like Makassar.This study represents the first comprehensive usability analysis of the Maxride application, providing valuable insights for both the company and the broader ride-hailing industry in Indonesia. It establishes a baseline for future usability research in this sector and demonstrates the application of the USE Questionnaire method in evaluating mobile app usability.